Establishment of Silvopasture in Existing Pastures - Jarek Nowak; Alan Long; Ann Blount (EDIS, 2004)
Silvopasture establishment requires a number of different management steps depending on previous land use. Planting trees in an existing improved pasture is the easiest way to start the system. Another possible scenario is to thin existing timber stands and plant or seed forage species among the remaining trees. This publication discusses establishment of silvopastoral systems in existing improved pastures. Information presented here is applicable to north Florida and other Southeastern states where tree and forage growing conditions are similar. This document is FOR107, one of a series of the School of Forest Resources and Conservation, University of Florida, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences. Publication date: June 5, 2003. Reviewed: July 2004.